The Effects of Individual Characteristics, Employees Commitment, Job Stress on Job Satisfaction and Employees Performance in PT. Timbul Persada in Tuban East Java - Tika Wahyunanti; I Dewa Ketut Raka Ardiana; Mohammad Sihab Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Human resources have a very important role in the company's activities. Therefore, the contribution of employees is needed for the company to achieve its objectives. The purpose of this study is to attest and analyze the influence of individual characteristics, employee commitment, job stress on job satisfaction and employee performance on PT. Timbul Persada Tuban East Java. This research uses the type of causality research with quantitative approach. Population taken in this research is all staff and manager at PT. Timbul Persada who is a permanent employee. Using total sampling technique with 95 employees. Data collection was done by distributing questionnaires. Data analysis technique used is SEM analysis with PLS program. the results of the study were accepting the hypotheses 1,3,4,5 and 7 while the hypotheses 2 and 6 were rejected.